A Comparison of Three English Textbooks in Japan by Correspondence Analysis - Uenishi, Koji (Archives of Business Research, 2025)
This paper explores the differences of the English textbooks for the seventh graders in Japan. Specifically, the seventh graders’ textbooks were analyzed using a readability tool and Correspondence Analysis (hereafter, CA). An analysis of the data suggests that, in terms of readability and content, there were both similarities and differences between the three textbooks. More precisely, regarding readability, the English textbook, New Crown is closer to the level of English textbook, New Horizon, and the level of textbook, Sunshine is lower than the other two textbooks. Also, concerning the content including vocabulary, CA shows that basically the three textbooks are different from each other.